Pemaknaan Puisi “Gadis Peminta-Minta” Karya Toto Sudarto Bachtiar melalui Pendekatan Semiotika dan Intertekstualitas - Siti Yulidhar Harunasari (LPPM STKIP Kusuma Negara, 2016)
As homo semioticus humans communicate to others through signs, one of which is poem. And to understand these signs, we could use a certain method to get the meaning of the poem, or the message sent by the writer. Riffaterre said that a poem says one thing, and means another. It means that a poem speaks indirectly so that the use of its language is of a different form. The indirectness is produced by displacing, distorting, or creating meaning. The true meaning of a poem can be achieved through the two levels or stages of reading, i.e. heuristic reading and retroactive reading. Toto Sudarto Bachtiar sees poverty –as reflected by his poem, “Gadis Peminta-minta” –as the manifestation of God’s affection that must be passed with patience. The intertextuality between “Gadis Peminta-minta” and “Kepada Peminta-minta” written by Chairil Anwar as the hypogram can be seen from the major theme in common, that is how both of them see poverty.